Accessible tourism through digital accessibility: a systematic literature review - Fernández-Díaz, Elena (2021)
Purpose. The number of people with disabilities or with special needs has increased worldwide. This is mainly due to the aging of the population and the global increase in chronic health problems associated with disability (World Health Organization, 2020). Tourism for all, and especially accessible tourism, is a generalized social demand that must be made possible by public authorities and companies in some way linked to the provision of tourist services (World Tourism Organization, 2016).